As Cartas ao amigo ausente de José Maria da Silva Paranhos: da política de neutralidade imperial à intervenção no Rio da Prata (1850-1851) - Silva, Gustavo Amaral Soares da (2022)
The presente research has as its the study of the Cartas ao Amigo Ausente of José Maria da Silva Paranhos, written to Jornal do Commercio (RJ) in the Years 1850 and 1851. Throught them we intend to understand the relations between the Empire of Brazil, the Argentine Confederation and Banda Oriental of Uruguay in this period. Important questions are the understanding and relevance of Paranho’s permormance in the press, which were the main reasons that led these states in formation to a belligerent state that culminated in the intervention of the Empire of Brasil Against Juan Manuel de Rosas and Manuel Oribe. This conflict is permeated by the demarcation of borders, limits and navigation, as well as the narratives and plots built to justify the possession of certain territory. Studies on the period and the work of Paranhos are rare in historiography, which justifies this work